An Intact Dorsomedial Posterior Arcuate Nucleus is Not Necessary for Photoperiodic Responses in Siberian Hamsters() - Teubner, Brett J.W. (Horm Behav, 2015)
Seasonal responses of many animal species are triggered by changes in daylength and its transduction into a neuroendocrine signal by the pineal gland through the nocturnal duration of melatonin (MEL) release. The precise central sites necessary to receive, transduce, and relay the short day (SD) fall-winter MEL signals into seasonal responses and changes in physiology and behavior are unclear. In Siberian hamsters, SDs trigger decreases in body and lipid mass, testicular regression and pelage color changes. Several candidate genes and their central sites of expression have been proposed as components of the MEL transduction system with considerable recent focus on the arcuate nucleus (ARC) and its component, the dorsomedial posterior arcuate nucleus (dmpARC). This site has been postulated as a critical relay of SD information through the modulation of a variety of neurochemicals/receptors important for the control of energy balance. Here the necessity of an intact dmpARC for SD responses was tested by making electrolytic lesions of the Siberian hamster dmpARC and then exposing them to either long days (LD) or SDs for 12 weeks. The SD typical decreases in body and fat mass, food intake, testicular volume, serum testosterone concentrations, pelage color change and increased UCP-1 protein expression (a proxy for brown adipose tissue thermogenesis) all occurred despite the lack of an intact dmpARC. Although the Siberian hamster dmpARC contains photoperiod-modulated constituents, these data demonstrate that an intact dmpARC is not necessary for SD responses and not integral to the seasonal energy- and reproductive-related responses measured here.